Governança corporativa e desempenho financeiro no brasil, chile e méxico - Pereira, Lucian Hendyo Max (2014)
One of the topics of current discussion in the field of Finance, but still open to a discussion of theoretical and empirical studies is the Corporate Governance. Sometimes related to discussions about the relevance of corporate governance practices on the financial performance of companies, especially in the context of emerging countries, works such as Klapper and Love (2004), Braga-Alves and Morey (2012), Claessens and Fan (2002) and Claessens and Yurtoglu (2013) investigated, in addition to the analysis on the prism of indicators of governance rights, verify that factors associated with governance (such levels legality of countries) could influence the performance of companies. In this perspective, the present study sought to investigate on the effects of corporate governance, expressed through the proposed by Carvalhal-da-Silva and Leal (2005) by examining the relevance in explaining corporate performance model. This research, unlike other works, left a recent methodological proposal (BRAGA-ALVES; MOREY, 2012), focusing on the relationship and interaction of institutional factors (risks specific to the business environment in the country level) and Governance. From a quantitative approach, focused on the correlation analysis - using the Pearson correlation coefficient of - and regression analyzes, using panel data, this study tested the research hypotheses related to the relationship between governance, political and institutional indicators financial performance of publicly traded companies in Brazil, Chile and Mexico in the period 2008-2012. With a total sample of 1245 observations and 249 firms, this study showed a statistically significant relationship between corporate governance and financial performance. Likewise, indicators of political and institutional differences proved significant in the estimated models. The results thus reaffirm that the literature already discussed: higher corporate governance practices are directly related to higher levels of financial performance. The end result of the work , in turn, showed that the interaction proposed by Klapper and Love (2004), between specific factors of the institutional environment of firms and corporate governance can influence, being even more robust than the financial performance of companies individual review of these factors. Among the main contributions of this work may be mentioned the expansion of the empirical results for developing countries , particularly Latin America, and the observed results , regarding the interaction of corporate governance and political- institutional factors of the countries on corporate performance. Among the limitations, in turn, provides an indication of those relating to the formatting of the database - data scarcity and limits to direct research - and the results of Carvalhal-da-Silva and Leal (2005) model